IMPLEMENTASI EXTENDED PRODUCER RESPONSIBILITY (EPR) DI PT. UNILEVER INDONESIA TAHUN 2022-2023 - Hasan, Mhd. Qur’anil; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Plastic waste has become an urgent environmental issue in Indonesia due to its rapid growth and adverse impacts on ecosystems. As one of the major producers of single-use plastic packaging in the fast-moving consumer goods (FMCG) sector, PT Unilever Indonesia contributes significantly to national waste generation. In response to Ministry of Environment and Forestry Regulation (Permen LHK) No. 75 of 2019, as well as external pressures from civil society and global sustainability standards, the company has implemented various initiatives under the Extended Producer Responsibility (EPR) framework. This research employs the Liberalism perspective, group-level analysis (multinational corporations), and Neo-Institutionalism theory using a qualitative case study method. Data were collected through literature studies from corporate reports, government regulations, academic publications, and environmental organization reports. The findings show that PT Unilever Indonesia, during 2022-2023, implemented EPR through three main strategies: reduce, reuse, and recycle. Programs such as packaging redesign, refill stations, and the use of post-consumer recycled plastic demonstrate the company’s commitment to circular economy principles. However, audits by the Ministry of Environment and Forestry (KLHK) indicate lower verified results than corporate claims, revealing a gap between internal reporting and government verification. The effectiveness of EPR implementation remains constrained by limited recycling infrastructure, low public participation, and inconsistent reporting methods. The success of EPR in Indonesia ultimately depends on synergy between producer innovation, regulatory oversight, and consumer engagement to strengthen the transition toward a credible circular economy. Keywords: plastic waste, Extended Producer Responsibility, Unilever Indonesia, circular economy, sustainability